Prefrontal Cortex Activity During Walking While Multitasking: An fNIR Study. (September 2013) - Hill, Audrey; Bohil, Corey; Lewis, Joanna; Neider, Mark
Previous work has demonstrated that walking while carrying out secondary cognitive tasks (e.g., talking on a cell phone) can lead to decrements in performance on both tasks. Studying these decrements in an ecologically valid setting has generally been limited to behavioral data (e.g., error rates, task completion times). Recently, the advent of portable neuroimaging technology – specifically, functional Near-Infrared spectroscopy (fNIR) – has made it possible to measure cortical activity while a participant is walking. We conducted an experiment using fNIR to measure cortical blood flow (in dorsolateral prefrontal cortex) while participants walked and carried out cognitive tasks of varying difficulty. Participants walked 25 feet on each trial, and performed either a low-load condition (counting backward by 1), or a high-load condition (counting backward by 7). Participants in the high load condition walked more slowly and performed the counting task more slowly and with more errors than those in the low load condition. fNIR results indicated a higher level of Prefrontal Cortex (PFC) activity during the high load condition. The difference in blood flow between load conditions was slightly more pronounced in the left hemisphere than in the right.